EDMODO AS ONLINE ASSESSMENT TOOL: TO IMPROVE EFL STUDENTS’ READING COMPREHENSION - Susanti, Arik; Nuria Putri, Diana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2022)
The study's objective was to examine if using Edmodo as an online assessment tool can improve students’ reading comprehension of recount text in e-learning. E-learning is considered an effective way to facilitate a better learning experience for students, especially in the assessment aspect. Formative assessment is a critical component of education that enable teachers and students to evaluate and improve their performance. Pre-experimental research with one group pre-test and post-test was applied in this study. The participants in the study were 36 tenth-grade senior high students in Krian, East Java. The instrument was pre and post-test consisting of objective and subjective tests. A paired sample t-test in SPSS 25 was used to analyze the data. The confidence interval of the difference used is 0.05. Therefore, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted if the value of Sig. (2-tailed) is less than 0.05. The result shows that online formative assessment through Edmodo can improve students’ reading comprehension skills. It is clear that Edmodo can serve as a prominent online assessment tool for students to assist them in improving their reading comprehension skills in e-learning. It is recommended teachers should continue to look for alternative platforms to conduct online assessments for e-learning to keep up with modern technological developments.